Contribution of tandem mass spectrometry to the diagnosis of lysosomal storage disorders. Issue 3 (19th March 2018) - Piraud, Monique; Pettazzoni, Magali; Lavoie, Pamela; Ruet, Séverine; Pagan, Cécile; Cheillan, David; Latour, Philippe; Vianey‐Saban, Christine; Auray‐Blais, Christiane; Froissart, Roseline
Abstract: Tandem mass spectrometry (MS/MS) is a highly sensitive and specific technique. Thanks to the development of triple quadrupole analyzers, it is becoming more widely used in laboratories working in the field of inborn errors of metabolism. We review here the state of the art of this technique applied to the diagnosis of lysosomal storage disorders (LSDs) and how MS/MS has changed the diagnostic rationale in recent years. This fine technology brings more sensitive, specific, and reliable methods than the previous biochemical ones for the analysis of urinary glycosaminoglycans, oligosaccharides, and sialic acid. In sphingolipidoses, the quantification of urinary sphingolipids (globotriaosylceramide, sulfatides) is possible. The measurement of new plasmatic biomarkers such as oxysterols, bile acids, and lysosphingolipids allows the screening of many sphingolipidoses and related disorders (Niemann–Pick type C), replacing tedious biochemical techniques. Applied to amniotic fluid, a more reliable prenatal diagnosis or screening of LSDs is now available for fetuses presenting with antenatal manifestations. Applied to enzyme measurements, it allows high throughput assays for the screening of large populations, even newborn screening. The advent of this new method can modify the diagnostic rationale behind LSDs.